EFFECT OF CIDR AND PGF 2a TO IMPROVE THE CONCEPTION RATE IN HOLSTEIN FRIESIAN CROSSBRED HEIFERS - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The objective was to evaluate the efficacy of an intravaginal progesterone insert and injection of PGF2 "’ for synchronizing estrus in Holstein Friesian heifers under field condition. The heifers were divided into two groups each consisting of eighteen (n=18) animals. Group I animals served as control and Group II animals were treated with an intra vaginal P4 device CIDR) for 9 days and PGF2 o: was given intramuscularly 24 hrs prior to CIDR removal. Fixed time artificial insemination was carried outat48 and 72 hrs after Cl DR removal. The overall conception rates obtained was 33.33 % in group I animals and 77. 77 % in group II animals treated with CIDR and PGF2alpha.